MEMAHAMI HAKIKAT ISLAM DAN REALITAS KAUM MUSLIM: UPAYA MEMBANGUN MASYARAKAT MADANI - Mufida, Luk Luk Nur (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2016)
Islam puts man in a dimension not only of individuals, but also in the social dimension as a member of a community. It is important for us to be able to give a bright picture of the main components in shaping the society we desire. In fact, some people still displays paradoxical attitudes in the dissemination of the teachings and values of Islam in social intercourse. For that, the basic concept of the Islamic community in fact laid on the principle of balance and harmony. Balance means a harmonious relationship between the vertical and horizontal dimensions, individual and social. global awareness of the resurrection of Islam who was covering the Muslim community today, by reviving the basic values of religion, many believed to be a way out of any slump. Despite the steps limping and panting, the Muslims began to have a deep awareness to develop and memperkasakan themselves as religious people are civilized and progress.